Modification method and test system for improving flashover voltage of epoxy resin under low temperature environment

By modifying nano SrTiO3 and adding it to epoxy resin, composite materials with high flashover voltage and excellent thermal conductivity were prepared, which solved the problem of low flashover voltage of epoxy resin in low temperature environments, and improved the Reliability of superconducting power devices.

CN115521575BActive Publication Date: 2025-02-25HEBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210994868.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-18
Publication Date
2025-02-25
Estimated Expiration
2042-08-18

AI Technical Summary

Technical Problem

In low temperature environments, the flashover voltage of the epoxy resin insulating material is low, resulting in a reduced reliability of the superconducting power device. It is difficult for existing modification methods to effectively improve the flashover voltage and maintain the excellent nonlinear conductivity and thermal conductivity of the material. .

Method used

By pretreating nano SrTiO3 and grafting modification of silane coupling agent KH550, modified nanoparticles with more uniform dispersion in epoxy resin were prepared, and composite materials were prepared by putting them into epoxy resin, combining with low temperature The test system of the vacuum box and the refrigerator is subject to temperature control.

Benefits of technology

It significantly improves the flashover voltage of epoxy resin in low temperature environments, avoids the problem of decreasing DC resistivity and reducing thermal conductivity of the material, and simplifies the insulation structure and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115521575B_ABST
    Figure CN115521575B_ABST
Patent Text Reader

Abstract

The present invention relates to a modification method and a testing system for improving the flashover voltage of epoxy resin under low temperature environment, comprising the following steps: step 1, pre-treating nano SrTiO3, removing moisture, and preparing a solution required for modification; step 2, modifying the nano SrTiO3 using the solution required for modification obtained in step 1, and removing moisture from the nano SrTiO3. The present invention adds modified nano SrTiO3 particles to an epoxy resin matrix, and the prepared composite material has strong nonlinear conductivity characteristics, can effectively inhibit charge accumulation, and thus improve the flashover voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy resin flashover voltage control, and relates to a modification method and a test system for improving the epoxy resin flashover voltage, in particular to a modification method and a test system for improving the epoxy resin flashover voltage under a low temperature environment. Background Art

[0002] Epoxy resin (EP) is a widely used insulating material, and its composite insulating material is often used as the insulation of superconducting terminal current leads. However, the good insulation performance of epoxy resin insulating material also leads to a slow charge dissipation process in a low-temperature environment. The charge injected through the electrode accumulates on the surface of the insulating material, aggravating the electric field distortion on its surface. It is easy to induce epoxy resin insulation flashover, which greatly reduces the reliability of the insulating equipment. Therefore, it is of great significance to study the modification method and test system for improving the flashover voltage of epoxy resin in a low-temperature environment to improve the operating reliability of superconducting power devices.

[0003] It is usually studied to improve the flashover voltage of insulating materials used in high-temperature superconducting power equipment in low-temperature environments in order to improve the stability of the entire insulation system. The most commonly used methods include: multilayer dielectric composite insulation structure composed of multiple layers of insulating materials with different dielectric properties, nano-SiC modification and ZnO doped insulating materials, etc.

[0004] A multilayer dielectric composite insulation structure composed of multiple layers of insulating materials with different dielectric properties has good nonlinear conductivity and can improve the flashover voltage of insulating materials in the temperature range of 80-300K. However, this method inevitably leads to an overly complex insulation structure, a large number of insulating materials, and a high cost. In addition, charges are easily accumulated at the interface, which in turn reduces the flashover voltage of the insulating material.

[0005] Nano-SiC modified epoxy resin has very strong nonlinear conductivity characteristics, which can improve the flashover voltage at low temperatures. However, studies have shown that if excessive nano-fillers are added to the epoxy resin matrix material to achieve nonlinear conductivity characteristics, it is very likely that the DC resistivity of the insulating material will drop too much, the glass transition temperature will decrease, and the nano-materials will agglomerate in large quantities, which will in turn reduce the flashover voltage.

[0006] The electrical properties of ZnO-doped insulating materials have been studied sufficiently, but doping with ZnO only has a significant effect on the electrical conductivity of the insulating materials and cannot enhance their thermal conductivity, which can easily lead to temperature concentration and thus reduce the flashover voltage of the insulating materials.

[0007] It can be seen that the existing technologies cannot provide a control method for effectively increasing the flashover voltage, and the modification process is difficult to control, which may easily lead to material damage due to excessive modification, and the purpose of increasing the flashover voltage cannot be achieved.

[0008] Therefore, how to develop a modification method and testing system that can significantly improve the flashover voltage of epoxy resin in low-temperature environments while ensuring the excellent nonlinear electrical conductivity and thermal conductivity of the composite material is a technical problem that needs to be urgently solved by technical personnel in this field.

[0009] After searching, no published patent documents identical or similar to the present invention were found. Summary of the invention

[0010] The purpose of the present invention is to overcome the shortcomings of the prior art and propose a modification method and a testing system for improving the flashover voltage of epoxy resin in a low-temperature environment, which can solve the problem of low flashover voltage of epoxy resin insulating materials in a low-temperature environment and improve the operating reliability of high-temperature superconducting power devices.

[0011] The present invention solves the practical problem by adopting the following technical solutions:

[0012] A modification method for increasing the flashover voltage of epoxy resin under low temperature environment comprises the following steps:

[0013] Step 1, pre-treating nano-SrTiO3, removing moisture, and preparing the solution required for modification;

[0014] Step 2: Modify the nano-SrTiO3 using the solution required for modification obtained in step 1, and remove moisture from the nano-SrTiO3.

[0015] Moreover, the specific steps of step 1 include:

[0016] (1) Take 200-250g of nano-SrTiO3 and place it in an evaporating dish. Dry it in a vacuum drying oven for 10-12h at a temperature of 120-125°C.

[0017] (2) Use a beaker to prepare the solution required for surface grafting modification, with the volume ratio of ethanol to pure water being 95:5. Continue to add silane coupling agent KH550 in an amount of 2% of the mass of the nanoparticles to be modified into the beaker, and then use an ultrasonic cleaner to perform ultrasonic dispersion treatment on the mixture for 30-40 minutes, with the temperature set at 70-75°C, to obtain the solution required for modification.

[0018] Moreover, the specific steps of step 2 include:

[0019] (1) While stirring the mixed solution at high speed using a heat-collecting magnetic stirrer, slowly add the nano-SrTiO3 to be modified, then seal the beaker and continue stirring at high speed for 5-6 hours, with the temperature set at 70-75°C;

[0020] (2) Pour the mixed solution into an evaporating dish and dry it in a vacuum drying oven for 12-13 hours at a temperature of 120-125°C. After the nano-SrTiO3 is completely dried, grind it carefully in a mortar. Then, take out the processed nanoparticles and store them, thereby obtaining modified nanoparticles with more uniform dispersion in the epoxy resin.

[0021] Moreover, after step 2, the method further comprises the following steps: step 3, placing the nano-SrTiO3 with more uniform dispersion after modification in step 2 into an epoxy resin body to prepare a composite material;

[0022] Moreover, the specific steps of step 3 include:

[0023] (1) preparing epoxy resin and modified nano-SrTiO3, placing the epoxy resin in a heat-collecting magnetic stirrer in a water bath to heat it to maintain its fluidity, setting the temperature to 30-35° C., and placing the modified nano-SrTiO3 in a vacuum drying oven for drying for 10-12 hours, setting the air pressure to -0.1 MPa, and the temperature to 120-125° C.;

[0024] (2) Add epoxy resin and curing agent into a flat-bottom flask in a mass ratio of 4:1, and then place it in a heat-collecting magnetic stirrer for high-speed stirring for 1-1.5 hours, and set the temperature to 60-65°C;

[0025] (3) According to the selected doping mass ratio of 0wt%, 5wt%, 10wt%, 15wt%, and 20wt%, the modified nano-SrTiO3 was weighed using a precision analytical balance and added to a flat-bottomed flask containing epoxy resin and curing agent solution, and then ultrasonic dispersion treatment was performed for 1-1.5h, and then the mixture was continuously stirred at high speed (60°C) for 1-1.5h in a heat-collecting magnetic stirrer, and degassed using a vacuum pump;

[0026] (4) Pour the above mixture into a horizontally placed stainless steel mold sprayed with a release agent, use a vacuum drying oven set at 75-80°C for pre-curing for 5-5.5 hours, then set the temperature to 140-145°C for curing for 5-5.5 hours, and the air pressure in the vacuum drying oven is -0.1MPa. After that, the mold can be demolded and taken out after natural cooling.

[0027] Moreover, the doping mass ratio of the nano-SrTiO3 in step 3 put into the epoxy resin body to prepare the composite material is: 10%-15%.

[0028] A low-temperature flashover voltage test system, comprising: a low-temperature vacuum box, in which a low-temperature flashover experimental device is placed, the low-temperature flashover experimental device comprising: a high-voltage finger electrode, a low-voltage finger electrode, an aluminum nitride ceramic plate bracket, and an experimental sample placed on the aluminum nitride ceramic plate bracket;

[0029] The aluminum nitride ceramic plate bracket includes: an upper plate and a lower plate, the upper plate and the lower plate are fixed together and spaced a distance apart in the vertical direction, the high-voltage finger electrode and the low-voltage finger electrode pass through the upper plate to fix the experimental sample on the lower plate; the upper end of the high-voltage finger electrode is connected to the high-voltage electrode on the low-temperature vacuum box, and the upper end of the low-voltage finger electrode is connected to the low-voltage electrode on the low-temperature vacuum box, an aluminum nitride ceramic sheet is placed under the experimental sample, and a flexible cold chain is placed under the aluminum nitride ceramic sheet, the flexible cold chain is externally connected to a refrigerator, and the temperature of the flexible cold chain is controlled by the refrigerator to control the temperature of the experimental sample.

[0030] Moreover, springs are mounted on the two finger electrodes to keep the bottoms of the two finger electrodes in close contact with the upper surface of the experimental sample.

[0031] Moreover, the high-voltage electrode is connected to a high-voltage direct current power supply and is used as a high-voltage electrode interface; the low-voltage electrode is connected to the earth and is used as a ground electrode.

[0032] Moreover, a temperature sensor is installed at the bottom of the lower plate of the aluminum nitride ceramic plate support to monitor temperature changes;

[0033] An insulating pad is placed in the low-temperature vacuum box below the temperature sensor; a vacuum pump is also installed on the low-temperature vacuum box to adjust the air pressure in the box.

[0034] Advantages and beneficial effects of the present invention:

[0035] 1. Compared with the multi-layer dielectric composite insulation structure, the composite material prepared by adding modified nano-SrTiO3 particles to the epoxy resin matrix in the present invention has strong nonlinear conductivity characteristics, can effectively inhibit charge accumulation, thereby increasing the flashover voltage, and has a simple insulation structure and reduces costs.

[0036] 2. Compared with the epoxy resin modified by nano-SiC, the composite material prepared by adding nano-SrTiO3 particles modified by silane coupling agent KH550 into the epoxy resin matrix has a better nonlinear coefficient and excellent thermal conductivity. It can avoid the negative effects of excessive drop in DC resistivity, lower glass transition temperature, and large-scale agglomeration of nanomaterials, and the flashover voltage is more significantly improved in low temperature environment.

[0037] 3. Compared with ZnO-doped insulating materials, the present invention enhances the thermal conductivity of the material by filling SrTiO3 nanoparticles in the epoxy resin, effectively suppresses the non-uniformity of conductivity, optimizes the electric field distribution, and improves the flashover voltage in a low temperature environment.

[0038] 4. In the present invention, silane coupling agent KH550 is used to carry out grafting modification treatment on nano-SrTiO3 particles, which effectively solves the problem that nano-SrTiO3 particles and epoxy resin organic polymer materials have poor compatibility during the doping process and are difficult to be infiltrated by epoxy resin, thereby increasing the dispersibility of nano-particles, thereby greatly improving the nonlinear conductivity characteristics.

[0039] 5. Compared with the existing flashover test system, the present invention can achieve temperature control in the range of 118K-300K through refrigerator and cold chain cooling. The low-temperature vacuum box is composed of double-layer organic glass to make the temperature more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a flow chart of a modification method for increasing the flashover voltage of epoxy resin under low temperature environment in the present invention;

[0041] Figure 2 It is the infrared spectrum of the nano SrTiO3 particles before and after the grafting modification treatment using the silane coupling agent KH550 in the present invention;

[0042] Figure 3 The present invention uses a scanning electron microscope (SEM) to observe the filling and dispersion effect of nano SrTiO3 particles in epoxy resin composite materials before and after grafting modification;

[0043] Figure 4 It is a schematic diagram of a low-temperature flashover voltage device in the present invention;

[0044] Figure 5 It is a composition diagram of the low temperature experimental device of the present invention;

[0045] Figure 6 It is a conductivity characteristic curve diagram of the EP / SrTiO3 nonlinear composite material with different filling contents at different temperatures in the present invention;

[0046] Figure 7 is a graph of thermal conductivity of the EP / SrTiO3 nonlinear composite material in the present invention in the range of 77K-300K;

[0047] Figure 8 It is a Weibull characteristic diagram of the flashover voltage of the EP / SrTiO3 nonlinear composite material under various temperature conditions of the positive polarity voltage in the present invention;

[0048] Fig. 9 It is a Weibull characteristic diagram of the flashover voltage of the EP / SrTiO3 nonlinear composite material under various temperature conditions of negative polarity voltage in the present invention;

[0049] Fig.10 It is a relative dielectric constant characteristic curve diagram of the EP / SrTiO3 nonlinear composite material with different filling contents at different temperatures in the present invention;

[0050] Description of reference numerals:

[0051] 1-high voltage finger electrode; 2-low voltage finger electrode; 3-plastic screw; 4-aluminum nitride ceramic plate bracket; 5-experimental sample; 6-aluminum nitride ceramic sheet; 7-flexible cold chain; 8-spring; 9-1-vacuum box; 9-2 vacuum box cover; 10-refrigerator; 11-vacuum pump; 12-temperature display; 13-high voltage electrode; 14-low voltage electrode; 15-barometer; 16-temperature sensor; 17-insulation pad; 18-valve. DETAILED DESCRIPTION

[0052] The embodiments of the present invention are further described in detail below with reference to the accompanying drawings:

[0053] A modification method for increasing the flashover voltage of epoxy resin under low temperature environment, such as Figure 1 As shown, the following steps are included:

[0054] Step 1, pre-treating nano-SrTiO3, removing moisture, and preparing the solution required for modification;

[0055] The specific steps of step 1 include:

[0056] (1) Take 200-250g of nano-SrTiO3 and place it in an evaporating dish. Dry it in a vacuum drying oven for 10-12h and set the temperature to 120-125℃;

[0057] (2) Use a beaker to prepare the solution required for surface grafting modification, with the volume ratio of ethanol to pure water being 95:5. Continue to add silane coupling agent KH550 in an amount of 2% of the mass of the nanoparticles to be modified into the beaker, and then use an ultrasonic cleaner to perform ultrasonic dispersion treatment on the mixture for 30-40 minutes, with the temperature set at 70-75°C, to obtain the solution required for modification.

[0058] Step 2, modifying the nano-SrTiO3 using the solution required for modification obtained in step 1, and removing moisture from the nano-SrTiO3;

[0059] (1) While stirring the mixed solution at high speed using a heat-collecting magnetic stirrer, slowly add the nano-SrTiO3 to be modified, then seal the beaker and continue stirring at high speed for 5-6 hours, with the temperature set at 70-75°C;

[0060] (2) Pour the mixed solution into an evaporating dish and dry it in a vacuum drying oven for 12-13 hours at a temperature of 120-125°C. After the nano-SrTiO3 is completely dried, grind it carefully in a mortar. Then, take out the processed nanoparticles and store them, thereby obtaining modified nanoparticles with more uniform dispersion in the epoxy resin.

[0061] Step 3, putting the nano-SrTiO3 with more uniform dispersion after modification in step 2 into an epoxy resin body to prepare a composite material;

[0062] The specific steps of step 3 include:

[0063] (1) preparing epoxy resin and modified nano-SrTiO3, placing the epoxy resin in a heat-collecting magnetic stirrer in a water bath to heat it to maintain its fluidity, setting the temperature to 30-35° C., and placing the modified nano-SrTiO3 in a vacuum drying oven for drying for 10-12 hours, setting the air pressure to -0.1 MPa, and the temperature to 120-125° C.;

[0064] (2) Add epoxy resin and curing agent into a flat-bottom flask in a mass ratio of 4:1, and then place it in a heat-collecting magnetic stirrer for high-speed stirring for 1-1.5 hours, and set the temperature to 60-65°C;

[0065] (3) According to the selected doping mass ratio of 0wt%, 5wt%, 10wt%, 15wt%, and 20wt%, the modified nano-SrTiO3 was weighed using a precision analytical balance and added to a flat-bottomed flask containing epoxy resin and curing agent solution, and then ultrasonic dispersion treatment was performed for 1-1.5h, and then the mixture was continuously stirred at high speed (60°C) for 1-1.5h in a heat-collecting magnetic stirrer, and degassed using a vacuum pump;

[0066] (4) Pour the above mixture into a horizontally placed stainless steel mold sprayed with a release agent, use a vacuum drying oven set at 75-80°C for pre-curing for 5-5.5 hours, then set the temperature to 140-145°C for curing for 5-5.5 hours, and the air pressure in the vacuum drying oven is -0.1MPa. After that, the mold can be demolded and taken out after natural cooling.

[0067] In this embodiment, when the doping mass ratio of the nano-SrTiO3 in step 3 to prepare the composite material is 10%-15%, the flashover voltage of the composite material is the highest.

[0068] In this example, a scanning electron microscope (SEM) was used to verify the filling and dispersion effect of the grafted modified nano-SrTiO 3 particles in the epoxy resin composite material.

[0069] A low temperature flashover voltage test system, such as Figure 3 and Figure 4 As shown, it includes: a low-temperature vacuum box, in which a low-temperature flashover experimental device is placed, and the low-temperature flashover experimental device includes: a high-voltage finger electrode, a low-voltage finger electrode, an aluminum nitride ceramic plate bracket, and an experimental sample placed on the aluminum nitride ceramic plate bracket;

[0070] The aluminum nitride ceramic plate bracket includes: an upper plate and a lower plate, the upper plate and the lower plate are fixed together and spaced a distance apart in the vertical direction, the high-voltage finger electrode and the low-voltage finger electrode pass through the upper plate to fix the experimental sample on the lower plate; the upper end of the high-voltage finger electrode is connected to the high-voltage electrode on the low-temperature vacuum box, and the upper end of the low-voltage finger electrode is connected to the low-voltage electrode on the low-temperature vacuum box, an aluminum nitride ceramic sheet is placed under the experimental sample, and a flexible cold chain is placed under the aluminum nitride ceramic sheet, the flexible cold chain is externally connected to a refrigerator, and the temperature of the flexible cold chain is controlled by the refrigerator to control the temperature of the experimental sample.

[0071] In this embodiment, springs are mounted on the two finger electrodes to keep the bottoms of the two finger electrodes in close contact with the upper surface of the experimental sample.

[0072] In this embodiment, the high voltage electrode is connected to a high voltage DC power supply and used as a high voltage electrode interface; the low voltage electrode is connected to the ground and used as a ground electrode.

[0073] In this embodiment, a temperature sensor is installed at the bottom of the lower plate of the aluminum nitride ceramic plate bracket to monitor temperature changes.

[0074] In this embodiment, a thermal insulation pad is placed in the low-temperature vacuum box below the temperature sensor.

[0075] In this embodiment, a vacuum pump is also installed on the low-temperature vacuum box to adjust the air pressure in the box.

[0076] The composition and functions of the components of the low temperature flashover voltage test system of the present invention are further described below:

[0077] A low-temperature flashover voltage test system, a low-temperature vacuum box, a refrigerator, a vacuum pump, a temperature display, and a low-temperature flashover experimental device is placed in the low-temperature vacuum box;

[0078] The low-temperature vacuum box is symmetrically provided with high-voltage electrodes and low-voltage electrodes. The high-voltage electrode is connected to a high-voltage DC power supply and used as a high-voltage electrode interface; the low-voltage electrode is connected to the earth and used as a ground electrode to ensure stable and reliable grounding of the test system. The vacuum box is used to simulate the low-temperature environment in the test.

[0079] A circular hole is provided on one side of the vacuum box, and the cold head side of the refrigerator passes through the circular hole. The refrigerator body is connected to the vacuum box by bolts, and an air cushion is provided at the connection between the refrigerator and the vacuum box to maintain air tightness.

[0080] The refrigerator is connected to one end of the flexible cold chain, and the other end of the flexible cold chain is in contact with the sample surface to control the temperature of the sample surface. The temperature display is connected to a BNC interface provided on the low-temperature vacuum box through a wire, and inside the low-temperature vacuum box, the BNC interface is connected to a temperature sensor.

[0081] The temperature sensor is adhered to the bottom of the flexible cold chain through thermal conductive silicone to monitor temperature changes.

[0082] The high-voltage finger electrode of the flashover experiment device is connected to the high-voltage electrode of the low-temperature vacuum box, and the low-voltage finger electrode is connected to the low-voltage electrode of the low-temperature vacuum box, and is used to perform a low-temperature flashover experiment.

[0083] In this embodiment, the low-temperature vacuum box is composed of double layers of organic glass, each layer of organic glass is 1 cm thick, and there is a vacuum layer with a length of 2 cm in the middle of the two layers of organic glass to improve the insulation capacity.

[0084] The low-temperature vacuum box includes: a box body and a box cover on the box body, a valve is provided on the box cover for releasing air to change the air pressure in the box; a barometer is also provided on the box cover for reading the air pressure value in the box at the time of the experiment; two copper column electrodes are symmetrically provided on the left and right end faces of the box body, one of which is used as a high-voltage electrode interface for connecting to the high-voltage DC source outside, and the other copper column electrode is used as a ground electrode to connect to the earth; a BNC interface is also provided on the end face of the low-temperature box body, and one side of the BNC interface in the box body is used to connect to the temperature display. A vacuum pump interface is also provided on the end face of the low-temperature box body, which is used to connect to the vacuum pump through the air guide tube to evacuate and release air to change the air pressure in the box.

[0085] The end surface of the low temperature box is also provided with a round hole and a threaded interface for connecting with a refrigerator to adjust the surface temperature change of the sample in the box.

[0086] In this embodiment, an insulating pad is placed in the low-temperature vacuum box to place the low-temperature flashover device and prevent the diffusion of temperature. The low-temperature flashover experimental device is used to perform low-temperature flashover experimental tests; it includes: two finger electrodes and an epoxy board bracket and an experimental sample; the epoxy board bracket includes: an upper plate and a lower plate, the upper plate and the lower plate are spaced a distance apart in the vertical direction, the four corners of the upper plate and the lower plate are fixed together by plastic screws and the two finger electrodes are fixed in preset positions; the high-voltage finger electrode is connected to the high-voltage electrode by a wire, and the low-voltage finger electrode is connected to the low-voltage electrode by a wire. The two finger electrodes pass through the upper plate to fix the sample on the lower plate, and a spring is mounted on the finger electrode to keep the bottom of the two finger electrodes in close contact with the upper surface of the EP sample, the upper surface of the aluminum nitride ceramic sheet in close contact with the lower surface of the sample, and the flexible cold chain in close contact with the lower surface of the aluminum nitride ceramic sheet. The temperature of the sample is controlled by controlling the temperature of the flexible cold chain by a refrigerator.

[0087] The following experiments verify that the present invention has beneficial effects:

[0088] The DC conductivity of EP / SrTiO3 nonlinear composite insulation material was tested by three-electrode method in accordance with GB / T 31838.2-2019. A circular sample with a thickness of 0.5 mm was used in the measurement process. The test electric field strength range was 1-15 kV / mm. The sample temperature was applied and maintained by a flexible cold chain. The test temperatures were 300 K, 245 K, 190 K, 135 K and 80 K respectively.

[0089] The flashover voltage of composite materials with different SrTiO3 nonlinear composite material doping amounts at temperatures of 300K, 245K, 190K, 135K and 80K was tested by the epoxy resin flashover voltage test system in a low temperature environment.

[0090] Figure 1 The present invention is a flow chart of a modification method for increasing the flashover voltage of epoxy resin under low temperature environment.

[0091] Figure 2This is the infrared spectrum of nano SrTiO3 particles before and after grafting modification with silane coupling agent KH550. The test adopts potassium bromide tablet method, and the equipment model is BRUKER VERTEX 80V2. In the infrared spectrum of nano SrTiO3 particles after grafting modification, the stretching vibration absorption peaks of -OH group and -NH2 group corresponding to wave number 3429cm-1 are significantly enhanced; the absorption peaks at 1634cm-1 and 1459cm-1 correspond to the variable angle vibration of -NH2 group and the stretching vibration of C=O double bond respectively; at the same time, the characteristic absorption peaks of Si-O and Si-O-Ti appear at 1061cm-1 and 966cm-1. The changes of the characteristic absorption peaks of the above infrared spectrum show that the process used in this paper successfully uses KH550 to graft modify nano SrTiO3 particles.

[0092] Figure 3 The filling and dispersion effect of the grafted modified nano-SrTiO3 particles in the epoxy resin composite material was verified by using a scanning electron microscope (SEM). The test morphology surface was the cross section of the sample manufactured by liquid nitrogen brittle fracture. The cross section of the epoxy resin nonlinear composite material was fish scale-like as a whole. The nano-SrTiO3 particles were in close contact with the epoxy resin matrix and there were no obvious defects. No agglomeration of nanoparticles was found in the epoxy resin composite material with low filling content, while a small amount of agglomerated nanoparticles was found in the sample with the highest filling content prepared, but most of the nano-SrTiO3 particles were still separated by the epoxy resin matrix, and there was no phenomenon of being penetrated by nano-SrTiO3 locally or even on a larger scale.

[0093] Figure 6 The nonlinear conductivity characteristic curves of EP / SrTiO3 nonlinear composite materials at different temperatures. Under various filling content conditions, the conductivity of the composite material increases with the increase of temperature, and the maximum increase multiple under low electric field strength is close to 8 times. The unfilled epoxy resin material does not show obvious nonlinear characteristics under 80-245K conditions, and only shows weak nonlinear characteristics under 300K conditions, and the threshold field strength is relatively high. With the increase of nano-SrTiO3 filling content, the nonlinear characteristics of the conductivity of epoxy resin composite materials become more and more obvious.

[0094] Figure 7This is the thermal conductivity curve of EP / SrTiO3 nonlinear composite material in the range of 77K-300K. With the increase of nano-SrTiO3 filling content, when the filling content is 5wt% and 10wt%, its thermal conductivity at 300K is 0.2535W / (m·K) and 0.2421W / (m·K), respectively, which is 19.26% and 13.83% higher than that of unmodified epoxy resin material. At this time, the thermal conductivity of EP / SrTiO3 nonlinear composite material at low temperature is improved to a greater extent, and at 80K, it is increased to 0.0880W / (m·K) and 0.1531W / (m·K), respectively, which is several times higher than that of unmodified epoxy resin material. When the filling content is further increased, the thermal conductivity of EP / SrTiO3 nonlinear composite material in the room temperature range also begins to increase significantly; the correlation between the thermal conductivity of the composite material and temperature is also weakened, and its ratio of decrease with decreasing temperature continues to decrease. When the filling content is 20wt%, the thermal conductivity of the composite material at 300K reaches 0.3368W / (m·K), and its thermal conductivity at 80K also reaches 0.1971W / (m·K), which is almost the same as the thermal conductivity of unmodified epoxy resin at 300K.

[0095] Figure 8 This is the Weibull distribution characteristic diagram of the flashover voltage amplitude of the EP / SrTiO3 nonlinear composite material under positive polarity voltage and different temperature conditions. The nano-SrTiO3 filling modification has a significant effect on the flashover voltage amplitude under various temperature conditions. Under the action of positive polarity voltage, the flashover voltage amplitude under various temperature conditions shows a trend of first rising and then falling. The flashover voltage amplitude under 300K conditions reaches a peak value of 17.9kV when the filling content is 10wt%. As the experimental temperature decreases, the filling content at which the flashover voltage amplitude reaches the peak value increases to 15wt%. The peak values ​​of the flashover voltage at 245K, 190K, 135K and 80K are 21.53kV, 24.17kV, 26.08kV and 27.23kV respectively.

[0096] Fig. 9The figure is the Weibull distribution characteristic diagram of the flashover voltage amplitude of the EP / SrTiO3 nonlinear composite material under negative polarity voltage and different temperature conditions. The nano-SrTiO3 filling modification has a significant effect on the flashover voltage amplitude under various temperature conditions. Under the action of negative polarity voltage, when the experimental temperature is high (300K and 245K), the flashover voltage amplitude shows a trend of first rising and then falling with the increase of filling content, and reaches a peak value of -20.54kV and -25.38kV when the filling content is 10wt%. When the experimental temperature is further reduced (190K, 135K and 80K), the change trend of the flashover voltage amplitude changes to increase with the increase of filling content, and the peak values ​​can reach -27.79kV, -30.82kV and -32.07kV respectively.

[0097] Fig.10 It is the relative dielectric constant characteristic curve of the EP / SrTiO3 nonlinear composite material with different filling contents at different temperatures in the present invention. At different temperatures, the relative dielectric constant of the composite material keeps monotonically increasing with the increase of the nano SrTiO3 filler content.

[0098] Table 1 shows the thermal conductivity and positive and negative polarity flashover voltage values ​​of the EP / SrTiO3 nonlinear composite material with different filling contents at different temperatures in the present invention. It is found that the thermal conductivity of the composite material increases with the increase of the nano-SrTiO3 filling content, and the positive and negative polarity flashover voltage first increases significantly with the increase of the nano-SrTiO3 filler, and then decreases slightly. When the nano-SrTiO3 filling content is between 10% and 15%, the flashover voltage of the composite material is the best.

[0099]

[0100]

[0101] Table 1

[0102] It should be emphasized that the embodiments of the present invention are illustrative rather than restrictive. Therefore, the present invention includes but is not limited to the embodiments described in the specific implementation modes. Any other implementation modes derived by those skilled in the art based on the technical solutions of the present invention also fall within the scope of protection of the present invention.

Claims

1. A modification method for increasing the flashover voltage of epoxy resin under low temperature environment, characterized in that: The following steps are involved: Step 1, pre-treating nano-SrTiO3, removing moisture, and preparing the solution required for modification; Step 2, modifying the nano-SrTiO3 using the solution required for modification obtained in step 1, and removing moisture from the nano-SrTiO3; After step 2, the method further comprises the following steps: step 3, placing the nano-SrTiO3 with more uniform dispersion after modification in step 2 into an epoxy resin body to prepare a composite material; The specific steps of step 1 include: (1) Take 200-250g of nano-SrTiO3 and place it in an evaporating dish. Dry it in a vacuum drying oven for 10-12h and set the temperature to 120-125℃; (2) using a beaker to prepare the solution required for surface grafting modification, the volume ratio of ethanol to pure water is 95:5, and the mass of silane coupling agent KH550 is continued to be added to the beaker, and then the mixture is subjected to ultrasonic dispersion treatment for 30-40 minutes using an ultrasonic cleaning machine, and the temperature is set to 70-75°C to obtain the solution required for modification; The specific steps of step 2 include: (1) While stirring the mixed solution at high speed using a heat-collecting magnetic stirrer, slowly add the nano-SrTiO3 to be modified, then seal the beaker and continue stirring at high speed for 5-6 hours, with the temperature set at 70-75°C; (2) pouring the mixed solution into an evaporating dish, drying it in a vacuum drying oven for 12-13 hours, setting the temperature at 120-125° C., grinding the nano-SrTiO3 carefully in a mortar after it is completely dried, and then taking out and storing the processed nano-particles, thereby obtaining modified nano-particles with more uniform dispersion in the epoxy resin; The specific steps of step 3 include: (1) preparing epoxy resin and modified nano-SrTiO3, placing the epoxy resin in a heat-collecting magnetic stirrer in a water bath to heat it to maintain its fluidity, setting the temperature to 30-35° C., and placing the modified nano-SrTiO3 in a vacuum drying oven for drying for 10-12 hours, setting the air pressure to -0.1 MPa, and the temperature to 120-125° C.; (2) Add epoxy resin and curing agent into a flat-bottom flask in a mass ratio of 4:1, and then place it in a heat-collecting magnetic stirrer for high-speed stirring for 1-1.5 hours, and set the temperature to 60-65°C; (3) According to the selected doping mass ratio of 10wt%-15wt%, the modified nano-SrTiO3 is weighed into a flat-bottom flask with epoxy resin and curing agent solution using a precision analytical balance, and then ultrasonic dispersion treatment is performed for 1-1.5h, and then the mixture is continuously stirred at 60°C for 1-1.5h in a heat-collecting magnetic stirrer, and degassed using a vacuum pump; (4) Pour the above mixture into a horizontally placed stainless steel mold sprayed with a release agent, use a vacuum drying oven set at 75-80°C for pre-curing for 5-5.5 hours, then set the temperature to 140-145°C for curing for 5-5.5 hours, and the vacuum drying oven pressure is -0.1MPa. After that, the mold is demolded and taken out after natural cooling; The low temperature environment is: 80K-245K.

Citation Information

Patent Citations

  • High-vacuum surface flashover voltage nano / epoxy resin composite dielectric

    CN105907044A

  • Device for testing insulation characteristics of low temperature insulation material based on conductive cooling

    CN109782146A